2013
DOI: 10.1038/aja.2013.27
|View full text |Cite
|
Sign up to set email alerts
|

Penoscrotal extramammary Paget's disease: surgical techniques and follow-up experiences with thirty patients

Abstract: To report the surgical management, complications and prognosis of patients with penoscrotal extramammary Paget's disease (EMPD) at different clinical stages. Between 2003 and 2008, a total of 30 male patients with penoscrotal EMPD were enrolled and evaluated. All enrolled subjects received frozen biopsy-guided local wide resection and immediate reconstruction. Patients were followed every 3 months postoperatively. Among the 30 patients who accepted and underwent frozen biopsy-guided local wide resection treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Poor prognostic factors include dermal invasion or metastasis via the lymphatic system. [7,29] Lymph node metastasis in most cases involves inguinal, peri-rectal, retroperitoneal, iliac, and para-aortic lymph nodes. Distant metastasis involves predominantly the liver, bone, lung, and suprarenal glands.…”
Section: Discussion Discussionmentioning
confidence: 99%
“…Poor prognostic factors include dermal invasion or metastasis via the lymphatic system. [7,29] Lymph node metastasis in most cases involves inguinal, peri-rectal, retroperitoneal, iliac, and para-aortic lymph nodes. Distant metastasis involves predominantly the liver, bone, lung, and suprarenal glands.…”
Section: Discussion Discussionmentioning
confidence: 99%
“…Some studies demonstrated that clear margins were highly relevant to whether local recurrence occurs 20 . Therefore major techniques including Mohs micrographic surgery, fluorescent dyes and frozen biopsy were extensively applied to defining the actual margin during surgery 25 . Although these methods could eventually ensure the clear margins, local recurrence persisted.…”
Section: Discussionmentioning
confidence: 99%
“…; eFigure in Supplement 1), and 135 articles were retained when (1) cases were limited to a single anatomic subtype (ie, perianal, vulvar, or penoscrotal) or (2) case-level data allowed distinction among these 3 anatomic subtypes (eTable in Supplement 1). Among the included articles, 113 (83%) included 10 or more cases of EMPD, suggesting reasonable cohort sizes considering the rarity of the disease. Cases that were metastatic on presentation were excluded.…”
Section: Methodsmentioning
confidence: 99%